Multicultural girlhood : racism, sexuality, and the conflicted spaces of American education - Thomas, Mary E. (Mary Elizabeth), 1970- (Global youth., 2011)
High school turf wars are often a teenage rite of passage, but there are extremes-as when a race riot at a Los Angeles campus in the spring of 2005 resulted in a police lockdown. In her fascinating book, Multicultural Girlhood, Mary Thomas interviewed 26 Latina, Armenian, Filipina, African-American, and Anglo girls at this high school to gauge their responses to the campus violence. They all denounced the outbreak, calling for multicultural understanding and peaceful coexistence. However, as much as the girls want everyone to just "get along," they also exhibit strong racist beliefs and validate.